Genetic variability and correlation analysis of exotic bread wheat accessions under early sown, irrigated and high fertility conditions - Prasad, S.V. Sai; Patidar, Manohar; Ambati, Divya; Singh, J. B.; Sharma, Brijesh; Tiwari, Dusyant; Patidar, C. P.; Malviya, Prakash (Annals of Agricultural Research, 2016)
Exotic bread wheat genotypes (132) received from CIMMYT, Mexico along with 3 check varietieswere evaluated for 2 years under early sown irrigated and high fertility conditions to identifygenotypes for coping with contemporary and projected climate extremes; and to estimate variabilityparameters, distribution and correlations for grain yield and its contributing traits. Significantgenotypic differences were observed for all the traits studied indicating considerable amount ofvariation among genotypes for each character. High to moderate heritability coupled with high tomoderate genetic advance as percentage of mean was exhibited for 5 traits viz., days to flowering,days to maturity, plant height, 1000 grain weight and spike length, which indicate that predominanceof additive gene action in the expression of these characters and consequently greater chance ofimproving these traits through simple selection. No. of tillers/m, biomass/plot, harvest index andgrain yield/plot showed low heritability along with low genetic advance, which suggested that thepresence of non-additive gene action and hence, improvement of these traits could be difficult throughdirect selection. Grain yield/plot showed significantly positive correlation with days to heading,plant height, spike length, no. of tillers/m, 1000 grain weight, biomass/plot and harvest index. Asa whole, genotypes viz., 45th IBWSN 1315, 29th SAWSN 3125 and 30th SAWSN 3036 showed highgrain yield along with superior yield contributing traits, hence, they can be utilized as a potentialdonors for improving grain yield in our wheat varieties under early sown, irrigated and high fertilityconditions